Evidence-based somatic treatment of depression in adults - Carlat, Daniel (Psychiatric Clinics of North America, 2012)
This article reviews recent studies and controversies about the effectiveness of antidepressant medications for depression. It is divided into three broad topics: (1) the heated controversy regarding how one should interpret 'efficacy studies' of antidepressants, that is, the standard placebo-controlled double-blind studies used by drug companies to gain Food and Drug Administration approval; (2) 'effectiveness studies,' open-label studies enrolling types of patients who are excluded from efficacy studies, focusing on one enormous study in particular—the STAR-D trial; and (3) the evidence base that can guide clinicians in the choice of antidepressants for particular patients. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: Antidepressant Drugs; Antidepressive Agents, Second-Generation; Clinical Trials as Topic; Depression; Drug Substitution; Drug Therapy; Drug Therapy, Combination; Evidence-Based Practice; Humans; Major Depression; Meta-Analysis as Topic; Neurotransmitter Uptake Inhibitors; Placebos; Serotonin Norepinephrine Reuptake Inhibitors; Serotonin Reuptake Inhibitors; Treatment Outcome; antidepressant drug therapy; major depression; selective serotonin reuptake inhibitors; serotonin norepinephrine reuptake inhibitors